RANCANGAN ALAT KHUSUS PELEPASAN DAN PEMASANGAN BEARING PADA TORQUEMETER SHAFT SUPPORT, HELICAL POWER TAKE-OFF GEARSHAFT, DAN PEMASANGAN BEARING DAN SPACER FUEL CONTROL SPUR GEARSHAFT ENGINE ALLISON 250-C20B - Fauzan Amarianda; Lilies Esthi Riyanti; Fatah Faturahman (Politeknik Penerbangan Indonesia Curug, 2019)
This Allison 250 C20 Series engine is one type of engine that is used as a practice equipment on Hangar 01 Aircraft Maintenance Training Organization. Special tools designed in this case are special tools in the form of 3 drifts that are used for the release and installation of bearings on the torque meter shaft support, helical power take-off gear shaft and fuel control spur gear shaft. Before entering the design discussion, the author will explain the theories that will be used in analyzing the force to be received and to design a special tool. An explanation of the theory used is intended to facilitate understanding the design process. The design criteria for a special tool in the form of a drift must be able to withstand the forces that will be given a pressure machine and dimensions designed for each drift according to the object to be removed or installed. In the design stage, the writer needs to analyze the force that will be received by each of the drifts, then after the calculation of the voltage to be received to determine the material of each drift. After calculating the authors chose S45C material to make the drift, because the material is able to withstand the stresses that occur during the release and installation of bearings.